PRESISI DAN AKURASI HASIL QUALITY CONTROL PADA PARAMETER PEMERIKSAAN GLUKOSA DARAH DI LABORATORIUM KLINIK RUMAH SAKIT X KOTA TASIKMALAYA - Meti Kusmiati; Rianti Nurpalah; Resa Restaviani (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
quality system is running properly and is carried out ensuring laboratory examination results. The purpose of this study was to see an how of the results of the precision and accuracy of the quality control parameters of blood glucose examination and to find out the mean, SD, CV and d% results. The research method used is descriptive quantitative analytic. The results obtained were quality control examinations of blood glucose in August CV (3.65%) d% (4.0%), September CV (2.96%) d% (4.5%), October CV (3.35%) d% (3.9%), November CV (2.0%) d% (3.5%), December CV (3.03%) d% (2.6%) and January CV (4.18%) d% (4.9%). The Ministry of Health has decided that limit maximum CV for checking blood glucose is still below the target value, namely <5%. The bias value (d%) of the blood glucose test was still below the target value set by ISO 15197, namely <5%. The results of this study it can be concluded that the maximum CV value and the bias value (d%) are still below the target value set by the Ministry of Health and ISO 15197, namely < 5%.